CO2MOVE Project: The New Brazilian Field Lab Fully Dedicated to CO2 MMV Experiments - Melo, Clarissa L.; De Moreira, Andréa Cristina; Goudinho, Flávio S.; Bressan, Lia W.; Constant, Marcelo J.; Oliva, Andresa [UNESP]; Chang, Hung K. [UNESP]; Nakaema, Walter M. [UNESP]; Vinter, Daniel P. [UNESP]; Ketzer, João Marcelo M.; Rosário, Fátima Do; Musse, Ana Paula S. (Elsevier, 2017)
After the Ressacada Project experience acquired from 2011 to 2015 when PUCRS, UNESP and other institutions conducted three controlled CO2 release experiments, PETROBRAS, the national oil company that is sponsoring the project, has launched a new challenge to its partners. The company stimulated the implementation of a new Brazilian experimental site where there will be a deepening of studies in geologically more complex conditions and more challenging from a technological point of view. The choice of an area inside PUCRS campus, in Viamão - Rio Grande do Sul state, was motivated by a predominantly clay subsoil and the privileged location of the site in terms of ease logistics and security, which is required for a project of this size that houses high-tech equipment with significant cost. The CO2MOVE project started at 2015 with the subsurface characterization of the site and the assembly and manufacture of an automated system for CO2 and gas tracers with injection capacity for 5 to 50 kg/day. Based on physical characterization studies and on numerical modeling that is being developed, the site infrastructure will be completed in the next months with the positioning of vertical injection wells, monitoring wells, and other equipment and monitoring mesh. Monitoring tools should be arranged in an area of approximately 100m2, occupying the entire region surrounding the injection wells. Fieldwork involving CO2 injection and monitoring should have a 60 days duration of which 15 days are for preliminary surveys (pre-injection), 30 days for injection and CO2 monitoring and the last 15 days for post-injection measurements. Following this work, the collected data will be analyzed in the university labs. Similarly to Ressacada Project, this experiment will run measurements of soil CO2 flux with accumulation chambers, CO2 turbulent fluxes with Eddy Covariance, subsurface gases and groundwater monitoring, and resistivity measurements. Other monitoring methods still not tested by the research team will be held as gas tracers monitoring and laser measurements.
Keywords: CO2; experiment; Monitoring; release